The impact of insomnia on depression: a prospective cohort study based on the UK Biobank - Wen, Zhiyu (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Major Depressive Disorder (MDD) is a serious global mental health condition that has gotten worse recently due to its influence on well-being and quality of life. Data from the World Health Organization (WHO) reveal a prevalence of 3.8% for depression globally. Depression’s link with various complications necessitates exploring its etiology for effective prevention and management. Insomnia, prevalent in 10-20% of adults, is closely associated with depression. The causal relationship between insomnia and depression is of particular interest. Using the UK Biobank database, a prospective cohort design investigated the independent association between insomnia and depression risk, adjusting for potential confounders. Data were analysed with descriptive statistics, ANOVA, χ2 tests, and multivariable Cox models. Several models accounted for confounders and evaluated insomnia’s relationship with depression. R Studio 2022.07.2 facilitated the analyses. The 173,809-participant cohort displayed diverse characteristics. This study, centered around Model 1, highlighted a significant association between depression and insomnia(P<0.05). Model 2 and Model 3 further validated this connection, maintaining a statistically significant difference in insomnia(P<0.05) after adjusting for additional factors. This study, utilizing the UK Biobank database, highlights the independent association between insomnia and depression risk. Findings underscore insomnia’s pivotal role across demographics, reinforcing the multifaceted nature of this link.